PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN ALAT PERAGA BATANG NAPIER UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI 164 PEKANBARU - Yulita, Kurnia Septi; Witri, Gustimal; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the low grade of third grader’s mathematics learning in SDN 164 Pekanbaru, seen from minimum criteria of mastery that defined by school policy is 75. 21 students of 34 in total did not achieve minimum criteria, with average grade value is 63,82. This condition is caused by the teacher learning method is lack of variaton. Beside, teacher does not use creative media in learning process. Those things make students lack of motivation and barely understand what they learn. Due to these issues, the action taken is cooperative learning using napier bone props. The purpose of this research is to improve students’ mathematics grade. The form of this research is a class action research. The subjects are III class students in SDN 164 Pekanbaru, consist of 34 students where there are 18 male and 16 female. Research instruments are test sheets, teacher and students observation sheets, and documentation files. The results showed improvement from each cycle. Teacher’s activities in first cycle was 62,5%, and increase to 66,7%. In second cycle was 83,33%, and increase to 91,7. Students’ activities in first cycle was 62,50%, and increase to 66,7%. In second cycle was 79,16%, and increase to 87,5%. Students’ average grade showed improvement too. Base grade was 63,82 increased to 66,17 on first test, and increased to 78,23 on second test. Based on these results, can be concluded that application of cooperative learning using napier bone media can improve students’ science grade of III class in SDN 164 Pekanbaru.Keyword : Cooperative learning, napier bone props, mathematics grade